To the Problem of Functioning of the Prepositions of Place in the Language of the Mass Media (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article analyses the mass-media texts in terms of the usage of prepositions. The peculiar attention is paid to the correctness of using the prepositions of place. It is pointed, that the prepositions of place possess certain shades of meaning and that is why journalists must be very precise in choosing these prepositions in every language situation.
Keywords: the prepositions of place; the contactive prepositions; the synonymic prepositions; the mass-media texts